Cloning of a Transglutaminase Gene from an Indonesian Streptomyces Strain - Seprianto Chaniago (Squalen, 2016)
Microbial Transglutaminase (MTGase, EC 2.3.2.13) is an enzyme that catalyzes the transfer of acyl group. Many microbial strains that produce MTGase belong to Streptomyces members. This research was aimed at cloning of a MTGase gene. PCR–based screening of ten MTGase-producing streptomyces isolates from soil in West Nusa Tenggara led to detection of one potential isolate, designated as TTA 02 SDS 14. The partial  MTGase-encoding gene (470 bp)  was amplified by PCR and sequenced. The sequence result indicate its similarity of 93 % with that of Streptomyces cinnamoneus. The 16S rRNA gene analysis showed its identity as Streptomyces thioleteus. Fosmid-based construction of a genomic library from the isolate  and subsequent screening led to the isolation of  a ~40-Kb fosmid harboring a MTGase gene.